Pengembangan Brand Image dengan Sistem Promosi pada Mrs Clean Laundry Mart di Kota Batam - Cuandra, Fendy; Agustian, Willien (Pakis Journal Institute, 2025)
Mrs Clean Laundry Mart is a micro, small, and medium enterprise (MSME) in Batam City that provides laundry services. To compete in a highly competitive market, a digital marketing strategy is needed to enhance brand image and attract more customers. This report discusses the implementation of promotions through social media and the inclusion of business locations on Google Maps to improve visibility and competitiveness. The methods used include interviews, observations, and SWOT analysis to identify issues and develop solutions. The implementation involves optimizing Instagram and TikTok accounts, creating promotional content, and registering the business location on Google Maps to make it more accessible to customers. The results show increased customer interaction and engagement on social media, as well as easier access to services via Google Maps. Digital marketing has proven effective in boosting brand awareness and business competitiveness, although further optimization of promotions and service innovations is still needed.